2018
DOI: 10.21608/ejchem.2018.5328.1470
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Reactions and Antitumor Activity of Certain 1,3-diphenylpyrazole-4-carboxaldehyde Derivatives

Abstract: I N continuation of our interest in synthesis of novel heterocycles with anticipated biological activity especially the antitumor activity.In this paper we have discussed synthesis and reaction of 1,3-diphenylpyrazol-4-carboxaldehyde 4 with acetophenone derivatives 1a-d, active methylene compounds, hydrazines and aniline derivatives to yield the expected derivatives 5ad. Also, a series of penta-substituted pyridine derivatives 15a-e have been synthesized by onepot three component cyclocondensation reaction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Previous literature reported that quinoline-2-thiones have a variety of applications such as synthetic intermediates (Jinbo et al, 1993;Joseph et al, 2002), bioactive molecules (Xavier, 1958), sulfur-nitrogen mixed donor ligands (Leeaphon et al, 1995;Nakano et al, 1977;Zhang & Matteucci, 1999), protective groups of thiols (Nakamura et al, (2002); Prabhu et al, 2008), and corrosion inhibitors (O'Connor & Lَ pez et al, 2014), as well as fluorescent sensors for metals, pH, and HNO (Albert & Barlin, 1959). Since pyridinedicarbonitrile nucleus is among the most widely used biologically and therapeutically important agents, this encourages us to attach it to quinoline ring system aiming to obtain novel compounds with anticipated biological activity (Amer El-Eraky et al, 2018;Amer Ramses et al, 2018). Kambe et al (1980) reported that the reaction of malononitrile with aromatic aldehyde and alkyl ketones in the presence of ammonium acetate and boiling benzene yields 2-Amino-4-aryl-3-cyanopyridines, and the reaction was assumed to proceed by formation of arylidenemalononitrile firstly which in turn reacts with alkyl ketones.…”
Section: Introductionmentioning
confidence: 99%
“…Previous literature reported that quinoline-2-thiones have a variety of applications such as synthetic intermediates (Jinbo et al, 1993;Joseph et al, 2002), bioactive molecules (Xavier, 1958), sulfur-nitrogen mixed donor ligands (Leeaphon et al, 1995;Nakano et al, 1977;Zhang & Matteucci, 1999), protective groups of thiols (Nakamura et al, (2002); Prabhu et al, 2008), and corrosion inhibitors (O'Connor & Lَ pez et al, 2014), as well as fluorescent sensors for metals, pH, and HNO (Albert & Barlin, 1959). Since pyridinedicarbonitrile nucleus is among the most widely used biologically and therapeutically important agents, this encourages us to attach it to quinoline ring system aiming to obtain novel compounds with anticipated biological activity (Amer El-Eraky et al, 2018;Amer Ramses et al, 2018). Kambe et al (1980) reported that the reaction of malononitrile with aromatic aldehyde and alkyl ketones in the presence of ammonium acetate and boiling benzene yields 2-Amino-4-aryl-3-cyanopyridines, and the reaction was assumed to proceed by formation of arylidenemalononitrile firstly which in turn reacts with alkyl ketones.…”
Section: Introductionmentioning
confidence: 99%